Exploring the Role of Decentralization in Resource Marginalization in Kenya - Walter Otieno, Ajwang’ Nicholas (European Scientific Journal, ESJ, 2023)
Against a background of increased decentralization, limited previous research examines its role in resource marginalization in Kenya. Specific objectives include identifying the socioeconomic sources of resource marginalization and identifying solutions to the socio-economic resource marginalization. The results of the study will improve our understanding of decentralization. Qualitative data was collected and analysed using thematic analysis. Quantitative data was collected and analysed using Statistical Package for the Social Sciences (SPSS). The study found that decentralisation has led to some form of marginalization. Recommendations for policy and further studies are made from the conclusions emanating from the academic study.